(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The increasing digitalization of education necessitates reconsidering primary mathematics instruction. This study explores the integration of blended learning in Latvian primary mathematics classrooms, addressing the evolving roles of students, teachers, and curricula in the digital age. Using a mixed-methods approach, we analyzed 60 mathematics lessons from 2022 to 2024 to assess student learning opportunities for blended learning. The findings indicate that while digital technologies are present, their pedagogical use remains limited. No observed lessons fully implemented blended learning, though some teaching profiles demonstrated elements of self-regulated and deep learning. Based on these findings and a review of the literature, we propose a conceptual framework for content and process integration for mathematics teaching in the digital age. The framework emphasizes the significant role of the digital dimension complementing the traditional didactic triangle of learner, teacher, and curriculum. This highlights and influences how we view self-regulation, communication, motivation, and process-content integration. Our study highlights the need for curricular adjustments and targeted professional development to better align teaching practices with the realities of digital transformation, ensuring students develop the necessary competencies for the future.